Knowledge leadership: Mobilizing management research by becoming the knowledge object. (July 2016) - Fischer, Michael D; Dopson, Sue; Fitzgerald, Louise; Bennett, Chris; Ferlie, Ewan; Ledger, Jean; McGivern, Gerry
This article explores contrasting forms of 'knowledge leadership' in mobilizing management research into organizational practice. Drawing on a Foucauldian perspective on power–knowledge, we introduce three axes of power–knowledge relations, through which we analyse knowledge leadership practices. We present empirical case study data focused on 'polar cases' of managers engaged in mobilizing management research in six research-intensive organizations in the UK healthcare sector. We find that knowledge leadership involves agentic practices through which managers strive to actively become the knowledge object – personally transposing, appropriating or contending management research. This article contributes to the literature by advancing the concept of knowledge leadership in the work of mobilizing management research into organizational practice.